Formulation and Stability of a 1% Clarithromycin-Based Topical Skin Cream: A New Option to Treat Buruli Ulcers? - Maria Sebti; Arnaud Schweitzer-Chaput; Salvatore Cisternino; Mélanie Hinterlang; Dimitri Ancedy; Sandrine Lam; Sylvain Auvity; Camille Cotteret; Olivier Lortholary; Joël Schlatter (MDPI AG, 2024)
There are more than 170 known species of non-tuberculous mycobacteria, and some are responsible for serious diseases in people infected with them. One of these is Buruli ulcers, a neglected tropical disease endemic in more than 33 countries and caused by Mycobacterium ulcerans, which infects skin tissue. Treatment consists of a long-term regimen combining the use of oral rifampin with another anti-tuberculosis drug (e.g., clarithromycin). Patients in these countries face difficulties in accessing and adhering to this therapy. This study investigates the feasibility of formulating stable, optimized clarithromycin as a topical cutaneous cream. The cream was formulated, and its stability was evaluated under different storage temperature conditions and using a stability indicator method. The results showed that the clarithromycin cream was stable for at least 60 days, even at extreme temperatures (40 °C). In conclusion, the data presented here demonstrate the stability of a new form of topical cutaneous clarithromycin, which may offer a new approach to the treatment of Buruli ulcers and clarithromycin-sensitive infections.